EDITORIAL - Acevedo Borrego, Adolfo (2014)
Industrial Data presents its readers distinguished the first volume of this academic year. The ISO 9001: 2008 is the international standard of quality, this certification has been obtained by the graduate unit, this process is presented by Jorge Luis Inche Mitma and Alfonso Ramon Chung Pinzas. The quality of healthcare services in a private institution is presented by Mary Leyzeaga Vargas and Agustin Mejias Acosta, both from the University of Carabobo, Venezuela